Relationship Of Body Image and Coping Behavior with Social Anxiety in Early Adult Women at RW 021 Pesona Anggrek Harapan Housing - Nurfaizi Ismail, Muhammad; Rama Dhanti, Diandha; Rahmadhanti Widyaputri, Dinaranda (Lafadz Jaya Publisher, 2024)
This research is quantitative research that aims to determine the relationship between body image and coping behavior with social anxiety in early adult women at RW.021 Pesona Anggrek Harapan Housing. The population in this research amounted to 140 subjects with 103 samples. The sampling method in the third study was Sample Random Sampling. The instrument of this study uses three Likert scale models, there are body image scale, coping behavior scale and social anxiety scale. The result of the analysis technique used was bivariate correlation, eta test, and dummy test. The result of the analysis data with bivariate correlation obtained a correlation coefficient (x1y) of r = -0.198; p = p<0.05 that there was a negative significant between body image with social anxiety , on the result of the eta test obtained a correlation coefficient (x2y) Fcount 9.3 and Ftable 0.02 that there was a positive between coping behavior with social anxiety, and then the dummy test result obtained correlation coefficient (R) of 0.216 and the coefficient of determination (R2) of 0.047 and p = 0.042 Which mean the relationship between body image and coping behavior with social anxiety.